Short Communication: Chemical composition and antioxidant activity of essential oil from Salvia hypoleuca at different growth stages - KIAN-DEHKIAN HABIB; BARZIN GITI; MAZOOJI ALI (Smujo International, 2016)
Abstract. Habib KD, Giti B, Mazooji Ali M. 2016. Chemical composition and antioxidant activity of essential oil from Salvia hypoleuca at different growth stages. Nusantara Bioscience 8: 145-149. The objective of this study was to investigate the chemical composition of essential oils extracted from Salvia hypoleuca aerial parts, wild type from Iran at various growth stages. Samples of the plant were taken during its vegetative, flowering and fruit stages. The different plant part samples were crushed and subjected separately to hydro-distillation. The obtained essential oil components were then analyzed by a combination of capillary GC and GC-MS. The DPPH method was used to evaluate antioxidant activity of the essential oils. Fifty-nine components were identified in essential oils. The major components of essential oils from the aerial parts were caryophyllene oxide (21.3-37.8%), the E-caryophyllene (13-18.1%), the bicyclogermacrene (6.7-13.1%), and germacrene D (3.8-10.3%). Antioxidant evaluations of the oils showed a moderate antioxidant activity with IC50 values of 32.6, 25.0, and 41.2 mg/mL of samples taken at the vegetative, flowering and fruit stages, respectively.